Changes in technical efficiency of the broiler production in Poland, 1994–2013. Issue 2 (4th March 2018) - Utnik-Banaś, K.; Żmija, J.; Krawczyk, J.; Połtowicz, K.
ABSTRACT: 1. The effects of changes in technical efficiency on the increase of broiler production are presented for the period 1994–2013 based on the panel data from seven farms located in southern and central Poland. A total of 766 cycles were analysed. 2. The Cobb–Douglas production function was used to assess the changes of output elasticities as well as technical changes in broiler production, for 5-year sub-periods separately. 3. Technical indices of broiler production significantly improved between years 1994–2013: feed conversion ratio decreased from 2.50 kg/kg to 1.78 kg/kg, mortality rate from 8.8% to 4.0% and daily weight gain increased from 37.1 g/d to 58.7 g/d, respectively. 4. Before accession to the EU, there was a substantial increase of fixed capital connected with modernisation of buildings and equipment. In the period 1994–2013, inputs of fixed capital per kilogram of livestock increased by 72% and at the same time the input of labour decreased by 56%. 5. Technical changes in years 1994–1998 contributed to a rapid production increase at a rate of 4.6% annually and only by up to 0.7% annually during 2009–2013. The slowdown of production rate increase after 2009 was partially caused by decreasing the stocking density.